2023
DOI: 10.2174/1871530322666220908154253
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Diabetes Mellitus in Patients with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by damage to multiple systems and a higher risk of cardiovascular disease. In addition, several studies have found that insulin resistance (IR) is more prevalent in SLE patients compared with controls, which increases the risk of prediabetes, type 2 diabetes mellitus (T2DM) and morbidity. The objective of this review was to summarize the most relevant evidence about the relationship among IR, T2DM and SLE, including the effects of pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The relationship between OAPS and abnormal INSR signaling is rarely reported. However, mounting evidence indicates that increased insulin resistance is more prevalent in other autoimmune diseases compared to controls, for example, in systemic lupus erythematosus (SLE) and rheumatoid arthritis 41 , 42 . Our discoveries from analyzing the circulating EV proteome prompt us to rethink the function of circulating proteins in disease pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OAPS and abnormal INSR signaling is rarely reported. However, mounting evidence indicates that increased insulin resistance is more prevalent in other autoimmune diseases compared to controls, for example, in systemic lupus erythematosus (SLE) and rheumatoid arthritis 41 , 42 . Our discoveries from analyzing the circulating EV proteome prompt us to rethink the function of circulating proteins in disease pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an immune disease. It has been found that IR is more prevalent in SLE patients than in controls ( 61 ), while serum vitamin D is negatively correlated with CD4+/CD8+ T cells ( 62 ), IFN-α levels ( 63 ), IL-17, IL-23 ( 64 ) in SLE patients. 25(OH)D 3 is further converted into 1,25(OH) 2 D 3 in the kidneys by 1α-hydroxylase, which is expressed by antigen-presenting cells ( 65 ), indicating an association of the immune microenvironment with active vitamin D production, suggesting that vitamin D may mediate the disease process in T1DM.…”
Section: Vitamin D and The Pathogenesis Of Diabetesmentioning
confidence: 99%
“…On the other hand, insulin levels and the homeostasis model assessment-estimated insulin resistance (HOMA-IR) index are increased in patients with SLE and SLE with MetS compared to healthy controls [27]. Studies in the literature have shown that SLE patients manifest deficient insulin secretion and a greater risk of IR.…”
Section: Metabolic Dysregulation In Sle and Its Biomarkersmentioning
confidence: 99%